Proceedings of the 17th Conference on Pattern Languages of Programs 2010
DOI: 10.1145/2493288.2493311
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-oriented knowledge model for architecture design

Abstract: Abstract. Software design patterns document the most recommended solutions to recurring design problems. Selection of the best design pattern in a given context involves analysis of available alternatives, which is a knowledge-intensive task. Pattern knowledge overload (due to the large number of design patterns) makes such analysis difficult. A knowledge base to generate available alternatives can alleviate the problem. In this paper, we propose a pattern-oriented knowledge model which considers four dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The IC1, IC2, EC4, EC5, and EC6 criteria were applied. Finally, after applying the three rounds and the IC and EC, 36 primary studies were obtained (see Table 3 ). The data extraction and synthesis processes for the 36 primary studies were conducted by using a form in which each study was identified with ID [13–15, 18, 22–53 ] and classified according to its context, validation, terminology, and usefulness in answering each research question.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IC1, IC2, EC4, EC5, and EC6 criteria were applied. Finally, after applying the three rounds and the IC and EC, 36 primary studies were obtained (see Table 3 ). The data extraction and synthesis processes for the 36 primary studies were conducted by using a form in which each study was identified with ID [13–15, 18, 22–53 ] and classified according to its context, validation, terminology, and usefulness in answering each research question.…”
Section: Methodsmentioning
confidence: 99%
“…The 41 papers obtained from conducting the review phase were coded as in [3, 11, 13–15, 18, 22–56 ]. They are the primary studies used to address the three research questions (see references and Complementary data (https://bit.ly/34rAYkm )).…”
Section: Reconstruction and Reverse Engineering Of Software Architementioning
confidence: 99%
See 2 more Smart Citations
“…2 Related work the ISO 42010, describing software architecture elements, is developed in Emery & Hiliard (2009) Emery and Hilliard (2009) and in Kumar & Prabhakar (2010) Kumar and Prabhakar (2010); and Antunes et al (2013) Antunes et al (2013) argues that different architecture domains can be integrated and analyzed through the use of ontologies.…”
mentioning
confidence: 99%